Creativity and intelligence: A link to different levels of human needs hierarchy?. Issue 5 (May 2018) - Neubauer, Aljoscha C.; Martskvishvili, Khatuna
Abstract: The relationship between creativity and intelligence has been intensely studied, but still is not clearly understood. Here, we aimed to investigate how creativity and intelligence are related to the different levels of human needs hierarchy. 342 participants completed a battery of instruments for intelligence and creativity as well as inventories for assessing the human needs satisfaction/frustration and self-actualization. We expected that creativity, as a characteristic of a self-actualized person should be related stronger to self-actualization needs, whereas intelligence should be related stronger to satisfaction/frustration, because of its role for humans' adaptation and survival. Results largely confirm expectations: Intelligence is positively related to lower needs, while creativity measures (divergent thinking, creative achievements and activities) show positive associations with higher levels of human needs. These results might contribute to the scientific debate regarding the distinction and the nature of the difference between intelligence and creativity.